Assessment of Placental Disposition of Infliximab and Etanercept in Women With Autoimmune Diseases and in the Ex Vivo Perfused Placenta. Issue 1 (8th April 2020) - Eliesen, Gaby A. M.; van Drongelen, Joris; van Hove, Hedwig; Kooijman, Nina I.; van den Broek, Petra; de Vries, Annick; Roeleveld, Nel; Russel, Frans G. M.; Greupink, Rick
Abstract : Tumor necrosis factor (TNF) inhibitors are increasingly applied during pregnancy without clear knowledge of the impact on placenta and fetus. We assessed placental transfer and exposure to infliximab ( n  = 3) and etanercept ( n  = 3) in women with autoimmune diseases. Furthermore, we perfused healthy term placentas for 6 hours with 100 µg/mL infliximab ( n  = 4) or etanercept ( n  = 5). In pregnant women, infliximab transferred into cord blood but also entered the placenta (cord‐to‐maternal ratio of 1.6 ± 0.4, placenta‐to‐maternal ratio of 0.3 ± 0.1, n  = 3). For etanercept, a cord‐to‐maternal ratio of 0.04 and placenta‐to‐maternal ratio of 0.03 was observed in one patient only. In ex vivo placenta perfusions, the extent of placental transfer did not differ between the drugs. Final concentrations in the fetal compartment for infliximab and etanercept were 0.3 ± 0.3 and 0.2 ± 0.2 µg/mL, respectively. However, in placental tissue, infliximab levels exceeded those of etanercept (19 ± 6 vs. 1 ± 3 µg/g, P  < 0.001). In conclusion, tissue exposure to infliximab is higher than that of etanercept both in vivo as well as in ex vivo perfused placentas. However, initial placental transfer, as observed ex vivo, does not differ between infliximab and etanercept when administered in equal amounts. The difference in placental tissue exposure to infliximab and etanercept may be of clinical relevance and warrants further investigation. More specifically, we suggest that future studies should look into the occurrence of placental TNF inhibition and possible consequences thereof.